Breaking Barriers: A Systematic Review of Women’s Entrepreneurship in the Tourism Industry - Hadriani Uli Tiur Ida Silalahi; Pantius Drahen Soeling; Chandra Wijaya (Publikasi Indonesia, 2025)
Women’s entrepreneurship in the tourism industry plays a crucial role in fostering economic development, gender equality, and sustainability. However, despite increasing participation, female entrepreneurs continue to face systemic barriers, including financial exclusion, socio-cultural constraints, limited business networks, and digitalization gaps. This systematic literature review (SLR) synthesizes existing research on the challenges, emerging trends, and future research directions in women’s entrepreneurship within the tourism sector. Findings highlight that gender biases in financial institutions, socio-cultural restrictions, and a lack of policy interventions significantly hinder the growth and sustainability of women-led tourism enterprises. Additionally, while digital transformation and sustainability trends present new opportunities, many women entrepreneurs remain excluded due to technological illiteracy, limited funding, and lack of access to digital platforms. The study identifies several research gaps, including the lack of longitudinal studies on women’s business sustainability, limited evaluations of gender-responsive policies, and insufficient exploration of post-COVID-19 recovery strategies for female-led tourism businesses. Moreover, the review highlights the need for comparative analyses of financial inclusion programs, digital entrepreneurship, and climate resilience strategies in tourism. Based on these insights, this study proposes future research directions focusing on financial accessibility models, gender-sensitive digital transformation strategies, and sustainable tourism policies tailored to women entrepreneurs. Policy recommendations emphasize the importance of inclusive financial frameworks, mentorship programs, digital upskilling, and stronger institutional support to foster a more equitable, resilient, and competitive tourism industry for female entrepreneurs.